2021
DOI: 10.1039/d1ra02511b
|View full text |Cite
|
Sign up to set email alerts
|

Sensing mechanism of a new fluorescent probe for hydrogen sulfide: photoinduced electron transfer and invalidity of excited-state intramolecular proton transfer

Abstract: Our theoretical results show that the fluorescence quenching of DFAN is caused by PET mechanism and the large Stokes shift fluorescence emission of DFAH is not due to the ESIPT mechanism. Due to the absence of PET process, enol structure emits strong fluorescence, which is inconsistent with the fluorescence mechanism in the experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…[116] This section will discuss QD-based strategies for biological H 2 S sensing (summarized in Table 3). Fluorescent-based QD probes for monitoring and imaging analytes of interest primarily rely on FRET [124] or photoinduced electron transfer (PET) [125] mechanisms. Sensitivity in these cases depends on the distance between the donor-acceptor or charge transfer chromophore-quencher pairs, respectively.…”
Section: Quantum Dot (Qd)-based Probesmentioning
confidence: 99%
“…[116] This section will discuss QD-based strategies for biological H 2 S sensing (summarized in Table 3). Fluorescent-based QD probes for monitoring and imaging analytes of interest primarily rely on FRET [124] or photoinduced electron transfer (PET) [125] mechanisms. Sensitivity in these cases depends on the distance between the donor-acceptor or charge transfer chromophore-quencher pairs, respectively.…”
Section: Quantum Dot (Qd)-based Probesmentioning
confidence: 99%
“…[3,4] So far, the generation of excited hydrogen bonds has become the focus of researchers, because the excited hydrogen bonds can affect the fluorescence sensing mechanism of compounds. [5][6][7][8][9][10][11] Thiazole compounds containing hydroxyl are a typical excited state intramolecular proton transfer (ESIPT) system with intramolecular hydrogen bonds. [12][13][14][15][16] Thiazole ring is an important type of five-membered aromatic heterocyclic ring.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, much attention has been directed toward the excited state intramolecular and intermolecular proton transfer (ESIPT) of hydrogen-bonded molecular systems from both theoretical and experimental aspects in recent years. [1][2][3][4][5][6][7][8][9] Particularly, due to the unique orientation and saturation properties, multiple hydrogen bonding interactions have played important roles in chemical, biological, and physical fields. [10][11][12][13] Over half a century of research history, it has been concluded the ESIPT reaction belongs to a kind of simple chemical behavior readily assessable for both quantum simulations and accurate measurement analyses.…”
Section: Introductionmentioning
confidence: 99%